189k views
3 votes
Suppose that f (x )is the inverse of g (x )and g (x )is the inverse of f (x ). Then f (g (x ))equals

User Doomsday
by
4.9k points

2 Answers

4 votes

Answer:

Since f(x) is the inverse of g(x) and g(x) is the inverse of f(x), then by definition


(f\circ g)(x)=f(g(x))=x\\(g\circ f)(x)=g(f(x))=x

User Fahad Alrashed
by
4.6k points
0 votes

Answer:

f(g(x)) = x

Explanation:

The inverse of a function is a function that "reverses" the other one, meaning that if I input a value x to the first function and get the result y on the second function, I can put the same y value to the second function and it will give me the first x value again.

In this problem we have that:

f(x) is the inverse of g(x) ⇒ f (x) = g⁻¹(x)

g(x) is the inverse of f(x) ⇒ g(x) = f ⁻¹(x)

The problem asks us to find f(g(x))

f(g(x)) = f(f ⁻¹(x)) = x

Therefore, f(g(x)) = x

User Kaisha
by
4.3k points